PERAN PSYCHOLOGICAL CAPITAL TERHADAP STUDENT ENGAGEMENT MAHASISWA KEPERAWATAN TINGKAT AKHIR [THE ROLE OF PSYCHOLOGICAL CAPITAL IN FINAL-YEAR STUDENT ENGAGEMENT] - Veronica Paula; Fransisca I.R Dewi (Universitas Pelita Harapan, 2020)
Introduction: The quality of education is measured through satisfactory learning achievements. Student success in learning is assessed based on learning outcomes. Students need to increase their desire to learn, thus students need to increase involvement in the learning process. The desire to learn can be increased by developing psychological strengths that exist in students which can be incorporated in one variable called psychological capital. The purpose of this study is to determine the role of psychological capital in student engagement during their senior year as nursing students. Research methods: This study was conducted using quantitative correlation methodology. The instruments used in this study were the Academic Psychological Capital Questionnaire (A-PCQ) and the University Student Engagement Inventory (USEI). Participants in this study were 130 senior nursing students. The results of the study: The result shows that the dimensions of psychological capital has a significant role in the involvement of students. The different dimensions of psychological capital included in the analysis are: (1) self-efficacy (p-value = 0,000), (2) resilience (p-value = 0.019), (3) optimism (p-value = 0.016) and (4) expectations (p- value = 0.558). Recommendation: Researchers can explore the internal factors in senior nursing students that help them develop self-efficacy, hope, resilience, and optimism. These dimensions are necessary for nursing students' progress to advanced learning and improvement of their achievements. Researchers then need to examine the impact of psychological capital in influencing leadership effectiveness, teamwork, and readiness to change.BAHASA INDONESIA ABSTRAK: Pendahuluan: Mutu pendidikan diukur melalui prestasi belajar yang tinggi dan memuaskan merupakan dambaan setiap mahasiswa untuk membanggakan orang tua. keberhasilan mahasiswa dalam belajar dinilai berdasarkan hasil belajar. Mahasiswa perlu meningkatkan keinginan belajar, sehingga mahasiswa perlu meningkatkan keterlibatan dalam proses pembelajaran. Keinginan untuk belajar dapat ditingkatkan dengan mengembangkan kekuatan-kekuatan psikologis yang ada dalam diri mahasiswa yang tergabung dalam satu variabel yaitu psychological capital. Tujuan penelitian: untuk mengetahui peran psychological capital terhadap student engagement mahasiswa keperawatan tingkat akhir. Metode penelitian: kuantitatif korelasi, alat ukur yang digunakan dalam penelitian ini adalah Academic Psychological Capital Questionnaire (A-PCQ) dan University Student Engagement Inventory (USEI). Partisipan pada penelitian ini berjumlah 130 mahasiswa keperawatan tingkat akhir. Hasil penelitian: menunjukkan peranan yang siginifikan bahwa dimensi psychological capital memiliki peranan terhadap keterlibatan mahasiswa adalah Efikasi diri (p-value= 0,000), resilien (p-value = 0,019), dan optimis (p-value = 0,016) sedangkan harapan (p-value =0,558). Rekomendasi: Peneliti selanjutnya maka peneliti dapat menggali faktor yang berhubungan dengan melakukan tinjauan pada aspek yang berasal dalam diri yaitu psychological capital dan tinjauan faktor yang berasal dari luar diri mahasiswa yaitu student engagement, pada mahasiswa keperawatan tingkat awal, untuk melihat peranan psychological capital dan student engagementnya. meneliti variable-variabel lain yang dapat diprediksi melalui psychological capital. Serta perlu menguji dampak dari psychological capital dalam memengaruhi efektivitas kepemimpinan, kerjasama tim, kesiapan untuk berubah.